2006
DOI: 10.1007/s11517-006-0045-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality evaluation of ultrasound imaging in the carotid artery based on normalization and speckle reduction filtering

Abstract: Image quality is important when evaluating ultrasound images of the carotid for the assessment of the degree of atherosclerotic disease, or when transferring images through a telemedicine channel, and/or in other image processing tasks. The objective of this study was to investigate the usefulness of image quality evaluation based on image quality metrics and visual perception, in ultrasound imaging of the carotid artery after normalization and speckle reduction filtering. Image quality was evaluated based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
12

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 25 publications
2
61
0
12
Order By: Relevance
“…Extensive validation of this technique showed that performance was limited by speckle noise. Even by adopting advanced techniques for speckle reduction [18] and wall clutter reduction [13], the automated local statistics based technique failed segmentation in about 8-10% of the images [21,26]. This is due to the fact that local statistics are very sensitive to noise; hence, a low signal-to-noise ratio precluded a correct initialization of the snake.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive validation of this technique showed that performance was limited by speckle noise. Even by adopting advanced techniques for speckle reduction [18] and wall clutter reduction [13], the automated local statistics based technique failed segmentation in about 8-10% of the images [21,26]. This is due to the fact that local statistics are very sensitive to noise; hence, a low signal-to-noise ratio precluded a correct initialization of the snake.…”
Section: Introductionmentioning
confidence: 99%
“…Retrieving images from large and varied collections using image content as a key is a challenging and important problem 6,7 . A new image representation is improved which provides a transformation from the raw pixel data to a small set of image regions which are coherent in color and texture space.…”
Section: Color and Texture-based Image Segmentationmentioning
confidence: 99%
“…El desempeño de un algoritmo de compresión se mide usando sistemas métricos encargados de determinar las diferencias entre dos imágenes (17). El resultado de estos sistemas métricos de calidad puede ser un número que representa la probabilidad de que el ojo humano pueda detectar una diferencia entre las dos imágenes o un número que cuantifica la similitud en su percepción.…”
Section: Clasificación De Los Algoritmos De Compresión Desde El Puntounclassified